Capacity in Transportation Systems: A Bibliometric of Local Road Capacity on the Middle City Scale - Pramadita, Moch. Galih; Azhary, Dejan Fauzan; Satrio, Rio; Toruan, Erni Sari Lumban; Hamdayani, Susanty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study presents a bibliometric analysis of research on transportation system capacity with a specific focus on local road networks in medium-sized urban areas. Using data sourced from reputable databases and analyzed through VOSviewer software, the study identifies research trends, collaboration networks, and dominant themes in this field. The results indicate a significant rise in scholarly interest over the past decade, particularly in addressing urban mobility, road congestion, sustainability, and the integration of emerging technologies such as artificial intelligence and smart transportation systems. The visualization of keyword networks and publication patterns highlights the interdisciplinary nature of transportation studies, involving engineering, urban planning, and environmental concerns. The findings are expected to provide valuable insights for researchers, policymakers, and urban planners in formulating future transportation strategies that are efficient, adaptive, and sustainable.